Improving mango production using partial root drying technique and organic fertilisation: Field and modeling study - Ayman El-Sayed; H. Hashem Mustafa; B.M.M. Bakr; R.E. Abdelraouf; R. Ragab; N.E. Mansour (Water Science, 2023)
ABSTRACTThe decreasing in water availability due to climate change can affect agricultural production. The water shortage problem led to the development of several water saving techniques. One of the waters saving techniques in irrigation is the partial root-zone drying (PRD) method. Tow field experiments accompanied by a modeling study were carried out during seasons 2020/2021 and 2021/2022, respectively, using four deficit irrigation strategies [FI (100% of full irrigation), DI1 (0.75FI), DI2 (0.5FI) where water was supplied to both sides of the mango trees and DI3 (Partial Root-zone Drying, PRD = 0.5FI) where water was supplied to a single side of each tree in an alternating manner)]. The four irrigation methods were designated as the study’s major plots. Then, for the purpose of adding compost, each main plot was divided into four smaller plots [NC (No-Compost), C12 (12 ton ha−1), C18 (18 ton ha−1) and C24 (24 ton ha−1)] to investigate the effects of such treatments on increasing water productivity, yield, and the quality of mango fruits. The results indicated that adding compost with PRD irrigation method decreased water stress throughout the root zone and increased the yield, water productivity and fruit quality. Compost addition C24 (24 ton ha−1) with PRD irrigation increased the amount of soil organic matter and microorganism activity when compared to other treatments. Additionally, C24 treatment improved mango quality under both FI and PRD treatments, the PRD technique enhanced fruit yields by 3.8% and 7.3% and water productivity by 51.6% and 53.8% for 2021 and 2022 seasons, respectively, compared to FI, while reducing the applied irrigation water by 50% for each season. In comparison to other irrigation strategies, the PRD strategy had shown superior outcomes in enhancing the yield, water productivity, and quality of mango yield. With the use of compost “C24” as organic matter fertilizer, PRD proved to be an effective dual technique to save water and increase productivity. Under both current and future water scarcity caused by climate change, it could be a successful adaptation technique. The SALTMED model produced accurate simulations of the soil moisture content, mango production, and water productivity during the two seasons.